2005
DOI: 10.1007/s11019-004-3530-z
|View full text |Cite
|
Sign up to set email alerts
|

Bodily integrity and male and female circumcision

Abstract: This paper explores the ambiguous notion of bodily integrity, focusing on male and female circumcision. In the empirical part of the study we describe and analyse the various meanings that are given to the notion of bodily integrity by people in their daily lives. In the philosophical part we distinguish (1) between a person-oriented and a body-oriented approach and (2) between four levels of interpretation, i.e. bodily integrity conceived of as a biological wholeness, an experiential wholeness, an intact whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 33 publications
0
35
0
9
Order By: Relevance
“…30,31 Apart from Muslims, it was reported that Jewish children also considered circumcision as blessed and culturally important and did not regard it as a punishment. 2 Our results showed that circumcision improved physical and social perception not only in childhood, but also in adulthood. After circumcision, our patients change of answers to the question concerning public bathrooms in the social phobia scale indicates that they had the anxiety of lack of circumcision in adulthood and regarded it as a physical defect.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…30,31 Apart from Muslims, it was reported that Jewish children also considered circumcision as blessed and culturally important and did not regard it as a punishment. 2 Our results showed that circumcision improved physical and social perception not only in childhood, but also in adulthood. After circumcision, our patients change of answers to the question concerning public bathrooms in the social phobia scale indicates that they had the anxiety of lack of circumcision in adulthood and regarded it as a physical defect.…”
Section: Discussionmentioning
confidence: 48%
“…Ancient depictions show that Australian Aborigines, Incas, Aztecs, Mayas, and ancient Egyptians performed circumcision. 1 Circumcision is performed as a religious ritual in most Muslim and Jewish countries, and it is also frequently performed in Middle-Eastern countries, as well as in the U.S. [2][3][4] World Health Organization reported that 30% of men worldwide and most Muslim men have been circumcised. 5,6 Circumcision has historical, religious, and cultural importance, as well as psychological significance.…”
Section: Introductionmentioning
confidence: 99%
“…Sünnet dünyada ve ülkemizde en sık uygulanan cerrahi işlemdir (1,2) . Tüm dünyada her yıl 13.3 milyon çocuk sünnet edilmektedir (2) .…”
Section: Introductionunclassified
“…Sünnet dünyada ve ülkemizde en sık uygulanan cerrahi işlemdir (1,2) . Tüm dünyada her yıl 13.3 milyon çocuk sünnet edilmektedir (2) . Amerika ve Avrupa'da sünnet tıbbi nedenlerden dolayı, Musevilerde dini zorunluluk nedeni ile özellikle ilk sekiz günde yapılmaktadır (3) .…”
Section: Introductionunclassified
“…And neither involves the treatment of disease, nor the correction of an acknowledged deformity. 24 Prima facie, then, at least according to this way of thinking, a similar medical-ethical analysis -based on conventional bioethical principles -would seem to apply to both.…”
mentioning
confidence: 98%